Students’ Perceptions in The Use of Artificial Intelligence Technology: The Influence of ChatGPT’s Voice in Speaking Class - Irma J.E Janis (Qalam : Jurnal Ilmu Kependidikan, 2025)
This study aimed to investigate students’ perceptions of the use of ChatGPT’s voice as an artificial intelligencebased learning tool in speaking classes. The research employed a descriptive qualitative design. Data were collected through semi-structured interviews with 19 first-year students of the English Education Department at the University of Papua. The interview data were analyzed through data reduction, data display, and conclusion drawing to identify emerging themes related to students’ experiences, preferences, and challenges.The findings indicated that the majority of students perceived the use of ChatGPT’s voice positively. Most participants reported feeling more comfortable, confident, and motivated when practicing speaking using ChatGPT’s voice. Sixteen students had prior experience using ChatGPT’s voice, while three students had no previous experience due to limited access or technological skills. All participants expressed a preference for using ChatGPT’s voice over traditional speaking instruction. However, several challenges were also identified, including limited vocabulary, difficulties in responding in English, and lack of access to suitable devices. Overall, the results suggest that ChatGPT’s voice has the potential to enhance speaking practice by providing an interactive, flexible, and supportive learning environment for EFL students.